Optimization of Citrus Pulp Waste-Based Medium for Improved Bacterial Nanocellulose Production - Carlotta Minardi; Davide Bersanetti; Essi Sarlin; Ville Santala; Rahul Mangayil (Microorganisms)
Bacterial nanocellulose (BC) has attracted significant attention across a wide array of applications due to its distinctive characteristics. Recently, there has been increasing interest in leveraging waste biomass to improve sustainability in BC biogenesis processes. This study focuses on optimizing the citrus pulp waste (CPW) medium to enhance BC production using Komagataeibacter sucrofermentans. The screening of initial medium pH, yeast extract, CPW sugar and inoculum concentrations was conducted using the Plackett–Burman design, with BC yield (mgDW/gCPW) as the model response. The significant parameters, i.e., CPW sugars and yeast extract concentrations, were optimized using response surface methodology, employing a five-level, two-factor central composite design. The optimized CPW-based growth medium resulted in a final yield of 66.7 ± 5.1 mgDW/gCPW, representing a 14-fold increase compared to non-optimized conditions (4.3 ± 0.4 mgBC/gCPW). Material characterization analysis indicated that the produced BC showed high thermal stability (30% mass retained at 600 °C) and a crystallinity index value of 71%. Additionally, to enhance process sustainability, spent baker’s yeast hydrolysate (BYH) was assessed as a substitute for yeast extract, leading to a final BC titer of 9.3 ± 0.6 g/L.